Pengaruh Penggunaan Mulsa Plastik terhadap Hasil Tanaman Cabai Rawit (capsicum frutescens l.) di Luar musim di Desa Kerta - I GEDE PUTU DARMAWAN; I DEWA NYOMAN NYANA; I GUSTI ALIT GUNADI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2014)
ABSTRACT Influence of Plastic Mulch on Crop Chili Pepper (Capsicum frutescens L.) Off Season in the Kerta village. Chili is one of the important horticultural commodities in Indonesia and has a high economic value. To maintain its supplies, cultivation technology that able to produce the commodities continuously is needed by applying technology in the off-season cultivation. This study aims to determine the effect of plastic mulch on chili crop in the off-season. The experimental design was used a randomized block design with 3 treatments and 9 replications. The treatment given is the use of mulch consisting of silver plastic mulch (MP), black plastic mulch (MH), and without mulch/control (K). The variables observed in this study, ware, plant height, number of branches, soil temperature, symptoms of viral diseases, and yield per hectare. The results showed the plastic mulch give good results on chili crop in the off-season. However, the highest results of the chili plants was in the silver plastic mulch treatments with plant height (95.64 cm), number of branches (13.11 piece), and yield (12.31 ton/ha). Keywords: chili pepper, off season, plastic mulch, yield